Rate discharge characteristics of LiNixCo1-xO2/EC : DMC, 1M LiPF6/LiC6 lithium ion batteries - Sulaiman, M.A.; Osman, Z.; Arof, Abdul Kariem (Journal of New Materials for Electrochemical Systems, 2003)
LiNixCo1-xO2 with 0.7 less than or equal to x less than or equal to 0.9 were used to fabricate lithium ion batteries. The rate discharge capabilities versus 0.2C of the batteries were studied by measuring the discharge profile of the batteries. From the results obtained, the battery fabricated from LiNi0.7Co0.3O2 showed the best performance at room temperature. At -10degreesC this battery was able to sustain more than 85 of its discharge capacity at room temperature. At 60degreesC the battery was able to sustain almost all its discharge capacity at room temperature.